Is the world becoming a “greener” place? empirics of green economic growth convergence and its determinants - Arogundade, Sodiq; Biyase, Mduduzi (Frontiers in Environmental Science, 2025)
Three decades after the Earth Summit in Rio de Janeiro, the world continues to grapple with the intertwined challenges of environmental degradation and the pursuit of inclusive, sustainable economic growth. This study investigates three key aspects of green economic growth: First, it examines whether global green growth is converging or diverging across regions. Second, it explores the fundamental drivers of regional differences in green growth, focusing on trade openness, CO2 emissions, and the transition to renewable energy. Finally, the study delves into the complex, nonlinear relationships between economic development and environmental sustainability. Using innovative methodologies such as PS club clustering and log-t regression analysis, the study analyzes production-based CO2 productivity data from 134 countries spanning 1995 to 2022. Contrary to conventional assumptions, the results reveal significant divergence in global green economic growth, suggesting that different regions are experiencing varied levels of success in integrating environmental and economic goals. These findings highlight the need for region-specific policies, emphasizing tailored strategies that promote sustainable development. Policymakers should prioritize fostering trade openness, accelerating the renewable energy transition, and implementing stricter environmental regulations, while also encouraging international collaboration to bridge the gap between advanced and developing economies.